Otto Wagner je na Solkanskem mostu pustil zanimiv pečat – o odkritju izvora mostne ograje - Humar, Gorazd (Gradbeni vestnik, 2024)
The railway bridge in Solkan, built in 1906, has the largest stone arch in the world. A fascinating and richly decorated cast-iron Secession-style fence was set up in the section above the arch. During World War I, when the bridge was demolished, it tumbled into the Soča River along with the arch. It remained there until 1999 when some of its essential parts were found during an extensive diving campaign. The recovered fence from the Solkan Bridge is identical to the one erected by Viennese architect Otto Wagner, father of the Vienna Secession, on the urban railway line in the centre of Vienna in 1901. An interesting fact: Otto Wagner entrusted the design of this railway line to the architect Jože Plečnik.
Keywords: Bohinj railway line; Bohinjska železniška proga; Dunajska mestna železnica; Jože Plečnik; Otto Wagner; R. Ph. Waagne; secesija; secession; Solkan bridge; Solkanski most; Vienna's urban railway